DOPO tethered Diels Alder clickable reactive silica nanoparticles for bismaleimide containing flame retardant thiol-ene nanocomposite coatings - OKTAY, BURCU; ÇAKMAKÇI, EMRAH (ELSEVIER SCI LTD, 2017)
The modification of nanoparticles (NPs) with functional groups that render them much more compatible with the polymeric matrices to prepare organic-inorganic hybrid materials is an active area of research. In this work, flame retardant and reactive nanosilica particles were prepared. First, nanosilica particles were coated with aminosilane and then reacted with furfural to introduce Diels Alder clickable sites. Finally, these reactive NPs were phosphorylated by reacting them with 9,10-dihydro-9-oxy-10-phosphaphenanthrene-10-oxide (DOPO). Different amounts of DOPO tethered Diels Alder clickable nanosilica particles (DDAS) were added to a bismaleimide resin containing thiol-ene based liquid pho-tocurable mixture. Bismaleimide acted as a crosslinker between the organic matrix and DDAS NPs. The effects of DDAS on the thermal and mechanical properties and the curing kinetics of the photocured coatings were investigated. The addition of BMI increased the Tg of the coatings from 40 to 78 degrees C with respect to the base formulation. The presence of BMI improved the distribution of DDAS NPs in the organic matrix. Moreover, the thermal and the flame retardancy of the hybrid coatings were improved. While the LOI of the base formulation was found as 21.6%, with the introduction of DDAS NPs the LOI of the hybrid coatings was increased up to 24.1%. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: DOPO; Click chemistry; Thiol-ene; PHOTOCURED HYBRID COATINGS; IMMOBILIZED SILICA; CROSS-LINKING; NANO-SILICA; CHEMISTRY; NETWORKS; SURFACE; FUNCTIONALIZATION; POLYMERIZATION; KINETICS